Extraction of By-Products from Nile Tilapia and Siamese Crocodile Scales - Hinsui, Jirapa; Tohmadlae , Patwarin; Klinlokai , Nattakan; Jantaratch, Nuttapong; Worawattanamateekul , Wanchai (Burapha Science Journal, 2026)
Nile tilapia scales are waste from chill / frozen fish fillets processing industries. Crocodile scales are waste from crocodile leather making process. However, valuable substances in the scales of both tilapia and crocodile could be extracted that can be used as raw materials for by-products in food industries. The objective of this study was to extract by-products from Nile tilapia and Siamese crocodile scales for food supplements. The composition of functional groups contained in dried Nile tilapia and Siamese crocodile scales was determined by Fourier-transform infrared (FTIR) Spectroscopy. Tilapia and crocodile scales were treated with sodium chloride, sodium hydroxide, sulfuric acid and citric acid before gelatin extraction at 50 ºC for 3 h then collagen type were evaluated by SDS-PAGE. The residue scales were treated with sodium hydroxide and hydrochloric acid for chitin-chitosan extraction then degree of deacetylation and FTIR Spectroscopy were analyzed. Sodium carbonate was added in sulfuric acid treatment solution for calcium precipitation then minerals contents and FTIR Spectroscopy were analyzed. FTIR result was showed that the scales contained collagen, calcium and chitin. The FTIR result related to extraction of gelatin, chitin-chitosan and calcium powder. Gelatin was collagen type I, chitin-chitosan was degree of deacetylation more than 40% and calcium powder contained calcium, phosphorus, magnesium and iron. Crocodile calcium powder contain high calcium (35.96 %). These extraction of valuable substances for food supplements were value and reduce waste and environment pollution.